2020
DOI: 10.1002/pat.4949
|View full text |Cite
|
Sign up to set email alerts
|

POSS nanoparticles as a potential compatibilizer for natural rubber/butadiene rubber blends

Abstract: In this study, it was aimed to investigate octavinyl‐polyhedral oligomeric silsesquioxane (OV‐POSS) incorporation into natural rubber (NR)/butadiene rubber (BR) elastomer blends as a potential compatibilizer. The effects of OV‐POSS loading levels on the thermal, mechanical, morphological, and dynamic‐mechanical properties of elastomer blends were explored. Fourier‐Transform Infrared Spectrometer (FTIR), Temperature Scanning Stress Relaxation (TSSR), and Differential Scanning Calorimetry (DSC) results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It can, therefore, be concluded that the incorporation of DDSQ-eter-4OH limited the molecular mobility around the glass transition temperature [59]. This effect may be caused by the increase in cross-linking of the ENR chains because of the introduction of additional reactive groups with the compatibilizer, which may indicate its incorporation into the structure of cross-linked rubber [41,42,54].…”
Section: Thermal Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…It can, therefore, be concluded that the incorporation of DDSQ-eter-4OH limited the molecular mobility around the glass transition temperature [59]. This effect may be caused by the increase in cross-linking of the ENR chains because of the introduction of additional reactive groups with the compatibilizer, which may indicate its incorporation into the structure of cross-linked rubber [41,42,54].…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…Typically, POSS particles measure between 0.6 and 1.2 nanometers in diameter and may contain certain functional groups [36]. There are considerable reports on the use of POSS molecules to function as a coagent [36] or compatibilizer [37][38][39][40][41][42] and improve thermal resistance [43,44] mechanical properties [45] and flame retardancy [46,47] of resulting hybrid materials. However, the usage of POSS as a compatibilizer is particularly interesting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that irrespective of the blend formulations, CB is more partitioned to the minor phase, that is, BR. In another study, octa vinyl-polyhedral oligomeric silsesquioxane (OV-POSS) was used as a compatibilizer for NR/BR blends [35]. DMA and contact angle studies indicated that the nanoparticles were located at the interface of the elastomers and contributed to improvements in the properties up to a certain loading.…”
Section: Introductionmentioning
confidence: 99%